Pemanfaatan Limbah Ampas Kopi sebagai Adsorben untuk Pengolahan Air Limbah Industri Tahu: Analisis Adsorpsi Batch dan Parameter Isoterm - Rara Ayu Lestary; Oki Alfernando; Sarah Fiebrina Heraningsih; Rosmawati Sipayung; Adelia Amanda; Alya Rizki Amelia; Ita Safitri; Septrinawati Tambunan; Tiamsa Sihotang; Karisma Ulfadeli; Tiara Bartisa Putri (Program Studi Teknik Kimia, Universitas Pamulang, 2025)
Coffee grounds waste can be utilized as a cost-effective and eco-friendly adsorbent for treating wastewater from the tofu industry. Batch adsorption experiments were conducted to evaluate the performance of coffee grounds as an adsorbent in removing pollutants from tofu wastewater. Different adsorbent doses (1 g, 2 g, and 3 g per 200 mL) were tested, and the quality of the wastewater was assessed based on changes in Total Dissolved Solids (TDS), turbidity, conductivity, and pH. The specific adsorption capacity (mg/g) and removal efficiency (%) decreased with increasing adsorbent dose. The overall removal of contaminants was most effective at a 3 g dose, resulting in a 47% reduction in TDS and an 80% decrease in turbidity. Adsorption equilibrium data were further analyzed using Langmuir, Freundlich, and Temkin isotherm models. The Langmuir model showed the best fit (R² = 0.999), indicating monolayer adsorption on a homogeneous surface. These results demonstrate that coffee grounds waste is a promising sustainable adsorbent, particularly for small and medium-scale tofu industries with limited resources for wastewater treatment.